THE The Samarinda Anticline: Surface Field Study At Sungai Siring, Samarinda, East Kalimantan - Dumex Pasaribu; Fikri Mustabidin; Epo Prasetya Kusumah (JURNAL TEKNOLOGIA, 2021)
This research was conducted in the Sungai Siring area, Samarinda, East Kalimantan and geographically located at 117 ° 13'19.44 "- 117 ° 17'52.19" E and 0 ° 23'53.58 "- 0 ° 27'13.91" S with a research area of ​​about 50 km2. The aim of this paper is to report data from surface study and hoped that this data can provide additional data to explain the process the forming of Samarinda Anticline. The data used in this paper were obtained from lineament analysis on the Digital Elevation Model (DEM) data and the results of geological mapping in the Sungai Siring area including outcrop observations, measurement of stratigraphic section, and measurement of geological structure data. According to the result of this study, the formation of structure in the research area begins with the compression force with the main stress trending southeast (SE) - northwest (NW) which causes the formation of an thrust fault as a blind fault which then accommodates the layer above it to fold in the late Miocene age when the Sandstone - Claystone units and Coal insert Sandstone units was deposited. Geological section restoration was carried out using the line length method in four section, the results of the restoration in the study area generally had a shortening of 11% - 43% (843 - 2831 meters), contraction ratio are 0.57 - 0.89, strain are 0.11 - 0.43, and the depth to detachment are 3816 - 5984 meters. The greater of the shortening causes the depth to detachment to be shallower and the folds that are formed are tighter than the smaller shortening. Keywords: Sungai Siring, Samarinda Anticline, Restoration